Diabetes mellitus may affect the long-term survival of hepatitis B virus-related hepatocellular carcinoma patients after liver transplantation - Zhang, Qing; Deng, Yong-Lin; Liu, Chang; Huang, Li-Hong; Shang, Lei; Chen, Xin-Guo; Wang, Le-Tian; Du, Jin-Zan; Wang, Ying; Wang, Pei-Xiao; Zhang, Hui; Shen, Zhong-Yang (World journal of gastroenterology : WJG, 2016)
AIM to determine whether diabetes mellitus(DM) affects prognosis/recurrence after liver transplantation(Lt) for hepatitis B virus(HBV)-related hepatocellular carcinoma(HCC). METHODS A retrospective study was conducted between January 2000 and August 2013 on 1631 patients with HBV-related HCC who underwent Lt with antiviral prophylaxis. Patient data were obtained from the China Liver transplant Registry(https://www.cltr.org/). to compare the outcomes and tumor recurrence in the HBV-related HCC patients with or without DM, statistical analyses were conducted using χ2 tests, Mann-Whitney tests, the Kaplan-Meier method, log-rank tests and multivariate step-wise Cox regression analysis. RESULTS Univariate analysis of 1631 patients who underwent Lt found overall 1-, 3- and 5-year survival rates of 79%, 73% and 71% respectively in the DM patients, and 84%, 78% and 76% in the non-DM patients respectively. Overall survival rate differences after Lt between the two groups were significant(P = 0.041), but recurrence-free survival rates were not(P = 0.096). By stratified analysis, the overall survival rates in DM patients for age > 50 years(P = 0.002), the presence of vascular invasion(P = 0.096), tumors ≤ 3 cm(P = 0.047), two to three tumor nodules(P = 0.007), Child-Pugh grade B(P = 0.018), and preLt alanine aminotransferase levels between 40 and 80 IU/L(P = 0.017) were significantly lower than in non-DM patients. Additionally, serum α-fetoprotein level > 2000 ng/m L(P = 0.052) was associated with a significant survival difference trend between DM and non-DM patients. Multivariate analysis showed that the presence of DM(P < 0.001, HR = 1.591; 95%CI: 1.239-2.041) was an independent predictor associated with poor survival after Lt. CONCLUSION HBV-related HCC patients with DM have decreased long-term overall survival and poor Lt outcomes. Prevention strategies for HCC patients with DM are recommended.